Clinical evolution and mortality of critically ill patients with SARS-CoV-2 pneumonia treated with remdesivir in an adult intensive care unit of Paraguay - Jessica Figueredo; Lorena Fontclara Lopez; Belinda Figueredo Leguizamon; Margarita Samudio; Marcelo Pederzani; Federico Fretes Apelt; Patricia Añazco; Ricardo Caballero; Hugo Bianco (BMC Infectious Diseases, 2024)
Abstract Background The health crisis due to Covid-19 led to the search for therapeutics that could improve the evolution of the disease. Remdesivir, an antiviral that interferes with viral replication, was one of the first to be used for the treatment of this pathology. Objective To determine clinical course and mortality of patients with severe SARS-CoV‐2 pneumonia treated with remdesivir, in comparison of those who didn’t receive the medication. Patients and methods Retrospective cohort study, with medical records review of COVID-19 patients, between August 2020 and August 2021. The subjects were divided into two groups, those who received remdesivir before or after admission to intensive care and those who didn’t. The primary outcome variable was mortality in intensive care. Results Of 214 subjects included, 109 (50,9%) received remdesivir. The median of days for the drug administration was 8 (2-20), IQR: 3. The bivariate analysis prove that the use of remdesivir was related with lower risk of develop Acute Respiratory Distress Syndrome (ARDS) (p = 0,019; OR: 0,521) and lower requirement of mechanical ventilation (p = 0,006; OR:0,450). Additionally, patients treated with remdesivir develop less kidney injury (p = 0,009; OR: 0,441). There was a total of 82 deaths, 29 (26,6%) in the remdesivir group and 53 (50,5%) in the control group [p < 0,001; OR: 0,356 (0,201-0,630)]. All the risk factors associated with mortality in the bivariate analysis were entered into the multivariate analysis by logistic regression, the use of remdesivir remained associated as an independent protective factor to mortality (p = 0.034; OR: 0.429). Conclusion Critically ill patients with SARS-CoV-2 pneumonia treated with remdesivir had a lower risk of death and need for mechanical ventilation and develop less ARDS as compared to the control group. No differences were found in the presentation of adverse effects.